Proteinaceous pancreatic lipase inhibitor from the seed of Litchi chinensis - Mhatre, Sveeta V. (Array, 2019)
A study of the pancreatic lipase inhibitory activity of a protein from the seed of Litchi chinensis was carried out. Protein was isolated by 70 % ammonium sulphate precipitation followed by dialysis. Lipase inhibitory activity of the protein was evaluated using both synthetic (p-nitrophenyl palmitate) and natural (olive oil) substrates. Protein at the final concentration of 100 µg/mL was able to inhibit 68.2 % pancreatic lipase on synthetic substrate and 60.0 % on natural substrate. Proteinaceous nature of the inhibitor was determined using trypsinization assay. Pancreatic lipase inhibitory protein was sensitive to 0.05 % trypsin treatment with the loss of 61.9 % activity. IC50 of this proteinaceous pancreatic lipase inhibitor was 73.1 µg/mL using synthetic substrate. This inhibitory protein was sensitive to pH, with the highest inhibitory activity at pH=8.0 and the lowest at pH=3.0. Protein was further analyzed using 10 % non-reducing sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) and, interestingly, it showed the presence of a single band of (61±2) kDa when stained with Coomassie brilliant blue. The isolated protein was finally crystallized to see its homogeneity by batch crystallization method. Crystals were well formed with distinct edges. The isolated protein showed good pancreatic lipase inhibitory activity.